Idiopathic retroperitoneal fibrosis diagnosed by endoscopic ultrasonography‐guided fine‐needle biopsy. Issue 1 (14th October 2020) - Kawakami, Yujiro; Takada, Yumemi; Ishigami, Keisuke; Hirano, Takehiro; Wagatsuma, Kohei; Masaki, Yoshiharu; Murota, Ayako; Motoya, Masayo; Tsujiwaki, Mitsuhiro; Takahashi, Hiroki; Nakase, Hiroshi
Abstract : We demonstrate a case, in which endoscopic ultrasonography‐guided fine‐needle biopsy (EUS‐FNB) was useful for determining the diagnosis of lesions of retroperitoneal fibrosis. In our case, accessing the retroperitoneal lesions by conventional percutaneous biopsy procedures was not feasible due to the difficulty of avoiding the inferior vena cava and ureter. We believe that our case demonstrates a unique approach for performing histological analysis in a challenging case.